Root-knot nematode (Meloidogyne incognita) and its management: a review - Subedi, Sudeep; Thapa, Bihani; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2020)
Root-knot nematode (RKN) Meloidogyne incognita stands out among the most harmful polyphagous endoparasite causing serious harm to plants, and distributed all over the globe. RKN causes reduced growth, quality and yield along with reduced resistance of the host against biotic and abiotic stresses. Infective second stage juvenile enters host roots with the help of the stylet and becomes sedentary getting into the vascular cylinder. Dramatic changes occur in host cells, making a specialized feeding site, induced by the secretion of effector protein by RKN. M. incognita can be controlled by nematicides, biocontrol agents, botanicals essential oils and growing resistant cultivars. Nematicides are no longer allowed to use in many parts of the world because of environmental hazards and toxicity to humans and other organisms. Researchers are concentrating on searching suitable alternatives to nematicides for effective management of M. incognita. This review mainly tries to explain the biology of M. incognita and different management options recommended in recent years. However, an effective and economical management of M. incognita remains an immense challenge.